علوم المکتبات والمعلومات فى ضوء الانتاج الفکرى العربى والأجنبى :دراسة تحلیلیة مقارنة للمفاهیم والمسمیات - د.رضا محمد النجار (المجلة الدولية لعلوم المكتبات والمعلومات)
A Comparative, Analytical and Descriptive study, Based on theConceptual Analysis within the Specialized Literature in Library, Information andKnowledge sciences, It aims to Reveal the Main Characteristics of this Literature,as well as to Observation the Relationship between this three Sciences, WithShedding Light the Views and Trends of Scientists and Specialists in theInterrelationships between this Sciences.